Phonotactic restrictions condition the realization of vowel nasality and nasal coarticulation: Duration and airflow measurements in Québécois French and Brazilian Portuguese. (July 2018) - Desmeules-Trudel, Félix; Brunelle, Marc
Highlights: The contexts in which contrasts occur have an influence on their phonetic realization. Phonotactically constrained nasality contrasts allow for more variability and more nasal coarticulation on vowels. Nasalized vowels are phonetically more variable in Brazilian Portuguese than in Québécois French. Abstract: This study examines the nasal airflow and duration patterns of vowels and nasal appendices in Québécois French (QF) and Brazilian Portuguese (BP) in order to determine if phonotactic restrictions on nasal and nasalized vowels have an influence on the realization of nasality contrasts. Results show that QF nasal vowels in syllables with more possible contrastive structures (Ṽ$ vs. VN$) show less variability than nasal vowels in syllables with more limited contrasts (ṼC$ does not contrast with *VNC$). Furthermore, nasal airflow of VN sequences rises earlier in syllable structures in which the distribution of nasal and nasalized oral vowels is restricted (VN$, but *ṼN$) than in those in which the distribution is not restricted (V$N and Ṽ$N are both possible). BP, which has stricter phonotactic restrictions on vowel nasality than QF, exhibits greater overall variability in the nasal airflow of V$N sequences and in the duration of nasal appendices. This supports the hypothesis according to which contrast in context influences the realization of phonological contrasts as well as of coarticulation.